2014
DOI: 10.5301/jabfm.5000190
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties and Biocompatibility of Oligochitosan Membrane Film as Wound Dressing

Abstract: These results indicate that the membrane film from O-C has potential application as a wound-dressing material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
(30 reference statements)
0
14
0
Order By: Relevance
“…Their pilot plant in Sepang (SIRIM incubation centre) is a GMP-compliant facility. Preparation of film was produced as described by Ujang and colleagues (2014-in press) 52 …”
Section: Methodsmentioning
confidence: 99%
“…Their pilot plant in Sepang (SIRIM incubation centre) is a GMP-compliant facility. Preparation of film was produced as described by Ujang and colleagues (2014-in press) 52 …”
Section: Methodsmentioning
confidence: 99%
“…[34] The in vitro WVTRs for all designs are as shown in Figure 3C. While these WVTR values are higher than the recommended reported in vitro WVTR to ensure optimal wound healing (2500 g d −1 m −2 ), [33] they are still lower than the WVTR of compromised skin. The WVTR values are also not excessively low so as to cause excessive retention of fluids at the wound bed.…”
Section: A Printability Value Less Than 1 Indicates Under Gelation Alongmentioning
confidence: 96%
“…The WVTR for normal human skin is reported to be 204 g d −1 m −2 , and this value can increase up to 5138 g d −1 m −2 for granulating wounds. [33] While a high WVTR is undesirable as it leads to dehydration of the wound, the WVTR should not be too low as well as that will result in the accumulation of wound exudates. [34] The in vitro WVTRs for all designs are as shown in Figure 3C.…”
Section: A Printability Value Less Than 1 Indicates Under Gelation Alongmentioning
confidence: 99%
“…Results from total bleeding and rate of bleeding in rats suggested that topical application of Opticell dressing with chitosan could be an available method in controlling bleeding correlated with wound debridement. COS was also used to design membrane films by blending various concentrations of glycerol with COS, where the membrane film exhibited high water vapor transmission rates and water absorption capacity thus could be applied to wound-dressing materials [123]. Decanoic acid grafted oligochitosan nanoparticles (CSO-DA NPs) was designed to explore its potential as a carrier for insulin.…”
Section: Biological Functions Of Cosmentioning
confidence: 99%